Ebola Epidemic in West Africa: A forgotten epidemic - Gboyega A Ogunbanjo (South African Family Practice, 2015)
On 23 April 2015, the World Health Organization (WHO) reported that the Ebola epidemic that started in West Africa about 18 months ago had infected 26 079 people, of whom 10 823 had died. The three worst hit countries were Guinea (2 358 deaths), Liberia (4 573 deaths) and Sierra Leone (3 877 deaths), and accounted for 99.86% of the fatalities.1 It is amazing that the West African Ebola epidemic is no longer headline news, and it appears as if life is back to normal in these three countries. However, the WHO has indicated that the decline in confirmed cases appeared to have stagnated, but warned that there was a need to increase efforts to stop Ebola virus transmission.